Multicenter study on the prevalence of colonization due to carbapenem-resistant Enterobacterales strains before and during the first year of COVID-19, Italy 2018-2020 - Teresa Fasciana; Alberto Antonelli; Alberto Antonelli; Gabriele Bianco; Donatella Lombardo; Giulia Codda; Emanuela Roscetto; Marianna Perez; Dario Lipari; Ignazio Arrigo; Elena Galia; Maria Rita Tricoli; et al. (Frontiers Media S.A., 2023)
BackgroundAmong multidrug-resistant (MDR) bacteria able to threaten human health, carbapenem-resistant Enterobacterales (CRE) have become a major public health threat globally. National and international guidelines point out the importance of active routine surveillance policies to prevent CRE transmission. Therefore, defining lines of intervention and strategies capable of containing and controlling the spread of CRE is considered determinant. CRE screening is one of the main actions to curb transmission and control outbreaks, outlining the presence and also the prevalence and types of carbapenemase enzymes circulating locally.ObjectiveThe purpose of this study was to outline the epidemiology of CRE colonization in Italy, detecting CRE-colonized patients at admission and during hospitalization, before and during the first year of COVID-19.Materials and methodsA total of 11,063 patients admitted to seven different hospitals (Bologna, Catania, Florence, Genoa, Naples, Palermo, and Turin) in Intensive Care Units (ICU) and other wards (non-ICU) located in the North, Center, and South of Italy were enrolled and screened for CRE carriage at admission (T0) and during the first 3 weeks of hospitalization (T1-T3). The study spanned two periods, before (September 2018-Septemeber 2019, I observational period) and during the COVID-19 pandemic (October 2019-September 2020, II observational period).ResultsOverall, the prevalence of CRE-colonized patients at admission in ICU or in other ward, ranged from 3.9 to 11.5%, while a percentage from 5.1 to 15.5% of patients acquired CRE during hospital stay. There were large differences between the I and II period of study according to the different geographical areas and enrolling centers. Overall, comparison of prevalence of CRE-positive patients showed a significant increased trend between I and II observational periods both in ICU and non-ICU wards, mostly in the Southern participating centers. KPC-producing Klebsiella pneumoniae was the most frequent CRE species-carbapenemase combination reported in this study. In particular, the presence of KPC-producing K. pneumoniae was reported in period I during hospitalization in all the CRE-positive patients enrolled in ICU in Turin (North Italy), while in period II at admission in all the CRE-positive patients enrolled in ICU in Catania and in 58.3% of non-ICU CRE-positive patients in Naples (both centers in South Italy).ConclusionThe prevalence of CRE in Italy highly increased during the COVID-19 pandemic, mostly in the Southern hospital centers. KPC-producing K. pneumoniae was the most frequent colonizing CRE species reported. The results of our study confirmed the crucial value of active surveillance as well as the importance of multicenter studies representing diverse geographical areas even in endemic countries. Differences in CRE colonization prevalence among centers suggest the need for diversified and center-specific interventions as well as for strengthening efforts in infection prevention and control practices and policies.